DISTINCTIVE REQUIREMENT OF PKCε IN THE CONTROL OF Rho GTPases IN EPITHELIAL AND MESENCHYMALLY-TRANSFORMED LUNG CANCER CELLS - Casado-Medrano, Victoria (Oncogene, 2019)
Diacylglycerol (DAG)/phorbol ester-regulated protein kinase C (PKC) isozymes have been widely linked to tumor promotion and the development of a metastatic phenotype. PKCε, an oncogenic member of the PKC family, is abnormally overexpressed in lung cancer and other cancer types. This kinase plays significant roles in proliferation, survival and migration; however its role in epithelial-to-mesenchymal transition (EMT) has been scarcely studied. Silencing experiments in non-small lung cancer (NSCLC) cells revealed that PKCε or other DAG-regulated PKCs (PKCα and PKCδ) were dispensable for the acquisition of a mesenchymal phenotype induced by transforming growth factor beta (TGF-β). Unexpectedly, we found a nearly complete down-regulation of PKCε expression in TGF-β-mesenchymally transformed NSCLC cells. PMA and AJH-836 (a DAG-mimetic that preferentially activates PKCε) promote ruffle formation in NSCLC cells via Rac1, however they fail to induce these morphological changes in TGF-β-mesenchymally transformed cells despite their elevated Rac1 activity. Several Rac Guanine nucleotide Exchange-Factors (Rac-GEFs) were also up-regulated in TGF-β-treated NSCLC cells, including Trio and Tiam2, which were required for cell motility. Lastly, we found that silencing or inhibiting PKCε enhances RhoA activity and stress fiber formation, a phenotype also observed in TGF-β-transformed cells. Our studies established a distinctive involvement of PKCε in epithelial and mesenchymal NSCLC cells, and identified a complex interplay between PKCε and small GTPases that contributes to regulation of NSCLC cell morphology and motile activity.